Design, development and testing of a tractor drawn semi-automatic rhizome planter for ginger and turmeric - MADHUKUMARA D.M; Dr. Manoj Mathew (Guide) (Tavanur 2017 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Design, development and testing of a tractor drawn semi-automatic rhizome planter for ginger and turmeric
Design, development and testing of a tractor drawn semi-automatic rhizome planter for ginger and turmeric